(untitled) (The Peerian Journal, 2025)
Since their inception, cinema and television have exhibited a vast plurality in their functions and applications, encompassing a wide range of phenomena, from realist and impressionist film schools to the technological and digital advancements that have profoundly influenced cinematographic imagery. These developments have relied on the intricate mechanisms of cinematic language, embedding form within content to convey deliberate concepts, thus establishing cinema and television as a significant artistic phenomenon. This phenomenon has occupied a vast space across multiple directions and artistic approaches, with distinct variations in aesthetic and dramatic treatment. Content creators have increasingly relied on cinema and television as expressive mediums laden with profound semiotic and aesthetic implications. In light of the above, the researcher seeks to establish the research problem: an inquiry into the modalities of Zionist thought in cinema and television